Analysis of Prospective Student Decision Making in Choosing a Study Program - Fananie, Zakia Alvin; Samawi, Ahmad; Maningtyas, Rosyi Damayani Twinsari (Proceedings Series of Educational Studies, 2024)
High school students certainly have different considerations and reasons for choosing and deciding to enter the PGPAUD department as a place to continue their education. This study aims to determine the knowledge, interest and reasons for high school students choosing or not choosing the PGPAUD Study Program. This research used descriptive approach with quantitative research type. SMAN 1 Talun was used as a research site, with a sample of 12th grade students totaling 168 students. In this study, the sampling procedure and technique used proportional random sampling technique. The data used was primary data by distributing questionnaires to respondents. The results showed that the knowledge of equivalent high school students related to PGPAUD study programs was still classified as moderate to low. The level of interest of equivalent high school students to continue their studies to PGPAUD is still classified as moderate to low. And the level of interest and reasons for students who choose the PGPAUD UM study program is still relatively low. The reasons for high school students who will choose the PGPAUD UM Study Program are mostly due to the desire to gain insight into early childhood education. The reasons for high school students who will not choose the UM PGPAUD Study Program are mostly due to the desire to choose studies in alternative fields and lack of interest in teaching early childhood. Keywords: Decision-Making; Prospective Students; Teacher Education For Early Childhood Education